2016
DOI: 10.4103/2249-4863.192359
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of antenatal mothers with the care provided by nurse-midwives in an urban secondary care unit

Abstract: Background:The satisfaction of antenatal women to antenatal services has rarely been studied in India. In a nation with a maternal mortality ratio of 178/100,000 live births, it is crucial to explore all avenues to reduce it.Aims:Our study aims to assess the pregnant women's satisfaction with regard to antenatal care services provided by nurse-midwives in an urban health center in South India.Methods:We administered a satisfaction of care questionnaire to 200 consecutive antenatal women attending the nurse run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
3
1
1
Order By: Relevance
“…Moreover, a study conducted in India showed that more than 90% of pregnant women who visited nurses were satisfied with antenatal care services. But in this study, only 31.8% of the mothers were satisfied with the health education on family planning [27].…”
Section: Satisfaction With Antenatal Care Servicescontrasting
confidence: 61%
“…Moreover, a study conducted in India showed that more than 90% of pregnant women who visited nurses were satisfied with antenatal care services. But in this study, only 31.8% of the mothers were satisfied with the health education on family planning [27].…”
Section: Satisfaction With Antenatal Care Servicescontrasting
confidence: 61%
“…12 The magnitude of women's satisfaction with ANC services ranges from 80% to 90% in Asian countries. [13][14][15] Studies in Africa showed that 42.94% of women were satisfied with ANC services. [16][17][18] Women's satisfaction with ANC services has varied in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…study was also lower than in studies conducted in Asian countries. [13][14][15] The discrepancy may be because the quality of ANC services differs from setting to setting and from time to time. It may also be due to satisfaction being subjective.…”
mentioning
confidence: 99%
“…This was in line with previous researches done in Sri Lanka and India. 24 , 29 The possible explanation for this finding was the low social experience for doctors compared to nurses. In fact, pregnant women were familiar with nurses during health education sessions where nurses alleviated their anxiety.…”
Section: Discussionmentioning
confidence: 99%